Financial Ratio Analysis as an Advisory Tool for Sustainable Pig Farm Management in Greece - Tsiouni, Maria; Kountios, Georgios; Kousenidis, Konstantinos; Kousenidis, Dimitrios; Tzamaloukas, Ouranios; Simitzis, Panagiotis E (My University, 2023)
This paper aims to provide pig farmers with the necessary information to guide strategic decisions through the development of a tool that allows them to calculate and control their production costs. A financial ratio analysis can be used as a starting point when assessing and improving a farm’s economic sustainability. The objective of the present article is to (1) provide insight into the financial ratios commonly used for pig farm assessments and (2) how they may be applied through an advisory tool to assess farm economic sustainability. Moreover, in this study, different financial ratios were examined to uncover trade-offs and synergies between them. Using the Farm Accountancy Data Network (FADN), we analyzed Spearman correlations between financial ratios. The correlation between these sets of indicators suggested that they could be used to estimate dairy farm economic sustainability. Our results showed that pig farms face a financial situation that can be improved. Pig farmers can benefit from this tool in multiple ways, by gaining an understanding of the costs and revenues leading to investment decisions, managing the risks, planning for potential growth, and having greater access to funding opportunities.
Keywords: sustainability assessment; advisory tool; pig farm management; financial ratio